Volume 1: Aircraft Engine; Fans and Blowers; Marine; Honors and Awards 2019
DOI: 10.1115/gt2019-91402
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Disciplinary Tool Coupling for the Determination of Turbofan Transients During Preliminary Design

Abstract: Over the past decades of preliminary aero-engine design a great effort has been invested in increasing steady-state efficiency to reduce missions fuel burn and thus CO2 emissions. Whilst pushing the performance cycle further to its limits previously minor deemed processes such as the transient behavior become more important because engines stability must still be granted for. It is therefore beneficial to integrate transient performance early into the overall aero-engine design tool chain to be able to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It was found that the additional heat flow from the engine metal to the air led to an increase in the specific heat (Cp). The lumped parameter method (LPM) has been widely utilized for heat soakage analysis due to its convenience [9][10][11][12][13][14]. In the LPM, each component is assumed as a mass node at the centre of real component geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the additional heat flow from the engine metal to the air led to an increase in the specific heat (Cp). The lumped parameter method (LPM) has been widely utilized for heat soakage analysis due to its convenience [9][10][11][12][13][14]. In the LPM, each component is assumed as a mass node at the centre of real component geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Vieweg et al developed a heat soakage model based on LPM. They compared their results with experimental data and an improvement in model accuracy was found when compared with the model without considering the heat soakage effect [11,14]. However, improvements can be made to consider cooling technologies and heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of control-system design and engine transient performance assessment as part of a multi-disciplinary preliminary design calculation has not been reported before in the public literature. Recent studies on novel propulsion systems have demonstrated the importance of considering transient performance as early as possible in the preliminary engine design phase in order to assess response and operability, but did not evaluate it as part of an overall cycle optimization at the aircraft-mission level [10] and with consideration of the design of the associated control system [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the early design stages, the need for fast and reliable multi-fidelity and multidisciplinary platforms (e.g., [2,3]), has made compressor mean-line (1D) models a valuable tool for the designer. They allow studying the effects of heat transfer [4], water evaporation, novel combustion concepts [5], and low-power operation on compressor aerodynamics [6].…”
Section: Introductionmentioning
confidence: 99%
“…• De-coupled: the higher fidelity code is used to generate compressor characteristics which are then used as data in the conventional 0D cycle code (e.g., [3]). • Semi-coupled: An iterative scheme is implemented, where the 0D cycle analysis provides boundary conditions to the 1D code and then the 0D component performance is updated according to the higher fidelity results.…”
Section: Introductionmentioning
confidence: 99%